Dyslipidemia in Psoriasis: A Case - Controlled Study - Kafle, Monique; Gyawlee, Madhu; Amatya , Amit; Kayastha, Bhaskar Mohan Meher; Upadhyaya, Smarika (Nepal Journal of Dermatology, Venereology & Leprology, 2021)
INTRODUCTION: Psoriasis is a chronic inflammatory condition of skin which can be associated with other ailments including dyslipidemia which is an abnormal serum lipid profile. OBJECTIVE: The aim of present study was to determine correlation between dyslipidemia and Psoriasis of patients visiting the Out-patient Department of Patan Hospital METHODS: Ninety patients were selected for study. Among them 30 patients with psoriasis were taken as cases and 60 patients that matched for age and sex with Psoriasis patients were taken as controls. The lipid profile that comprised four parameters: serum High-density Lipoprotein, Low-density Lipoprotein, Total Cholesterol and Triglyceride were determined and compared for both case and control groups. RESULTS: More than 95% of the psoriatic patients had dyslipidemia. The odds of dyslipidemia among Psoriatic patients were 1.709 times higher compared to control group (p <0.001). Among the parameters, results showed High-density lipoprotein was significantly lower while Triglyceride was significantly higher among the cases compared to controls with p value of 0.012 and 0.001 respectively. The risk factors like smoking and alcohol were present in higher proportions among the patients with dyslipidemia but it failed to reach statistical significance. With increase in duration of Psoriasis and PASI scores, lipid parameters i.e., Total cholesterol, triglyceride and Low-density lipoprotein increased while High density lipoprotein decreased but this correlation was insignificant. CONCLUSION: This study showed Dyslipidemia is significantly higher among patients with Psoriasis especially lipid profile parameters Triglyceride and total cholesterol. Thus, timely screening and management of dyslipidemia among Psoriatic patients might be helpful in prevention of future cardiovascular events.